STIM1 promotes migration, phagosomal maturation and antigen cross-presentation in dendritic cells - Paula Nunes-Hasler (Nature Portfolio, 2017)
STIM proteins sense Ca2+ depletion in the ER and activate store-operated Ca2+-entry (SOCE) in response, a process associated with dendritic cell functions. Here the authors show STIM1 is the major isoform controlling SOCE in mouse dendritic cells and provide a mechanism for its requirement in antigen cross-presentation.